AN IMPLANT FOR A VISUAL CORTICAL STIMULATOR - Coulombe, Jonathan; Hu, Yamu; Gervais, Jean-Franҫois; Sawan, Mohammad (Proceedings of the Canadian Engineering Education Association (CEEA), 2011)
We present the design of an implantable micro-stimulator intended for a cortical visual prosthesis. The device is composed of several integrated modules to be assembled on a thin and flexible substrate providing placement flexibility on the cortex. The stimulator provides the user with significant usage flexibility, supplying biphasic current pulses using either monopolar or bipolar configurations, with single or distributed return electrode, and having a fixed or dynamic reference voltage. Monitoring of electrode-tissue interface condition is possible by measuring both simulation currents and voltages at any electrode for enhanced safety, and for enabling troubleshooting after implantation. In order to avoid erroneous stimulation to be executed, potentially caused by the implant's wireless transcutaneous power transfer, constant parameters stored in volatile memory are constantly monitored, and in case of data corruption, stimulation is automatically disabled. A power efficient recovery and regulation circuit is proposed for providing dual supply voltages. Also, a bidirectional wireless link with data rates up to 1.5 Mbps and 500 kbps, downlink and uplink respectively, has been designed for use with a 13.56 MHz carrier. Performances attained with a prototype, combined with the stimulator module's configurable communication protocol, are suitable for a cortical implant having more than 1000 stimulation sites, which is expected to be sufficient for providing blind subjects with a useful vision.